Laterally substituted symmetric and nonsymmetric salicylideneimine-based bent-core mesogens - Findeisen-Tandel, Sonja; Weissflog, Wolfgang; Baumeister, Ute; Pelzl, Gerhard; Murthy, H. N. Shreenivasa; Yelamaggad, Channabasaveshwar V. (Beilstein Journal of Organic Chemistry, 2012)
Bent-core mesogens have gained considerable importance due to their ability to form new mesophases with unusual properties. Relationships between the chemical structure of bent-core molecules and the type and physical properties of the formed mesophases are relatively unknown in detail and differ strongly from those known for calamitic liquid crystals. In this paper symmetric and nonsymmetric five-ring salicylideneaniline-based bent-core mesogens are presented, and the effect of lateral substituents attached at the outer phenyl rings (F, Cl, Br) or the central phenyl ring (CH3) on the liquid-crystalline behaviour and on the physical properties is studied. Corresponding benzylideneaniline-based compounds were additionally prepared in order to study the influence of the intramolecular hydrogen bond. The occurring mesophases were investigated by differential scanning calorimetry, polarising microscopy, X-ray diffraction and dielectric and electro-optical measurements. The paper reports on new findings with respect to the structure–property relationships of bent-core mesogens. On one hand, the disruptive effect of laterally substituted halogen atoms, F, Cl and Br, on the mesophase behaviour of three isomeric series was much lower than expected. On the other hand, an increase of the clearing temperature by 34 K was observed, caused by small lateral substituents. The electro-optical behaviour, especially the type of polar switching and corresponding molecular movements, is sensitive to variations in the molecular structure.
Keywords: antiferroelectric smectic phases; bent-core mesogens; electro-optical behaviour; liquid crystals; salicylideneanilines